Slow fluorescent indicators of membrane potential: a survey of different approaches to probe response analysis - Plásek, J; Sigler, K (Journal of photochemistry and photobiology. B, Biology, 1996)
Basic tenets related to the use of three main classes of potentiometric redistribution fluorescent dyes (carbocyanines, oxonols, and rhodamines) are discussed in detail. They include the structure/function relationship, formation of nonfluorescent (H-type) and fluorescent (J-type) dimers and higher aggregates, probe partitioning between membranes and medium and binding to membranes and intracellular components (with attendant changes in absorption and emission spectra, fluorescence quantum yield and lifetime). The crucial importance of suitable probe-to-cell concentration ratio and selection of optimum monitored fluorescence wavelength is illustrated in schematic diagrams and possible artifacts or puzzling results stemming from faulty experimental protocol are pointed out. Special attention is paid to procedures used for probe-response calibration (potential clamping by potassium in the presence of valinomycin, use of gramicidin D in combination with N-methylglucamine, activation of Ca-dependent K-channels by A23187, the null-point technique). Among other problems treated are dye toxicity, interaction with mitochondria and other organelles, and possible effects of intracellular pH and the quantity of cytosolic proteins and/or RNA on probe response. Individual techniques using redistribution dyes (fluorescence measurements in cuvettes, flow cytometry and microfluorimetry of individual cells including fluorescence confocal microscopy) are discussed in terms of reliability, limitations and drawbacks, and selection of suitable probes. Up-to-date examples of application of slow dyes illustrate the broad range of problems in which these probes can be used.
Keywords: fluorescenční barviva; membránové potenciály; Membrane Potentials; Fluorescent Dyes; Animals; lidé; Humans; zvířata